The Practicality of Problem Solving E-Book in Plant Growth and Development Material to Train Critical Thinking Skills - Dwi Ayulistiana; Yuliani Yuliani (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2020)
The ability to solve problems or problem-solving steps include identify, define, enumerate, analyze, list, and self-correct. Each of them can be used to practice critical thinking skills. The purpose of this research was to produce a practical problem-solving based e-book on plant growth and development topic in order to facilitate students' critical thinking skills. This study used a 4-D development model namely Define, Design, Develop, and Disseminate, but the disseminate stage was not conducted. Limited trials were conducted on 20 students of class XII IPA 2 of SMA Negeri 16 Surabaya. The research instruments were readability sheet, test sheet, questionnaire sheet for student and teacher respons. The data were analyzed quantitative descriptively. The practicality of the e-book was reviewed from the results of the readability test, critical thinking skills, student and teacher responses. The results of the study indicated that the readability test results categorrized as level 12 which was suitable for use by XII grade high school students. E-Book was stated to be very good for practicing critical thinking skills of 85,26% completeness indicators. Student and teacher responses showed a very positive results with a score of 97.4% and 100% respectively. Keywords: practicality of e-books, critical thinking skills, plant growth and development.